Implementing a mobile stroke unit program in the United States: why, how, and how much? - Rajan, Suja S; Rajan, Suja; Baraniuk, Sarah; Parker, Stephanie; Wu, Tzu-Ching; Bowry, Ritvij; Grotta, James C (JAMA neurology, 2015)
There are many ways a mobile stroke unit (MSU) might prove valuable for patients with ischemic and hemorrhagic stroke, such as earlier recognition, more accurate triage, improved management of blood pressure and other critical physiological variables, and eventually earlier implementation of effective therapies. The MSU may be particularly valuable for treatment of patients with acute ischemic stroke with tissue plasminogen activator (tPA) within 4.5 hours of symptom onset, the most evidence-based effective emergency treatment for the most prevalent stroke diagnosis. To review existing data on prehospital stroke treatment, especially relevant to MSU technology, to identify gaps in our understanding of MSU feasibility, especially relevant to applying the MSU strategy in the United States, and to describe the Houston MSU program and clinical trial. Published data from English-language journals in PubMed from 1995 to present reviewing early treatment with tPA and prehospital stroke evaluation and treatment. The MSU may result in an overall shift toward earlier evaluation and treatment with tPA, particularly into the first hour after symptom onset, leading to substantially better outcomes. As a result of improved clinical outcomes owing to earlier treatment, the costs of an MSU program may be offset by a reduction in the costs of long-term stroke care and an increase in quality-adjusted life-years, thereby supporting more widespread use of this technology. To make MSU deployment more practical, the vascular neurologist aboard the MSU must be replaced by a remote vascular neurologist connected to the MSU by telemedicine, reducing manpower requirements and costs. The MSU strategy could dramatically transform the way acute stroke is managed in the United States. A prospective study evaluating the logistics, outcomes, and cost-effectiveness of this approach is needed and under way.